Diversity and distribution of coral lifeforms in Tioman Island - Kamarumtham, Kharina; Ahmad, Zuhairi; Halid, Nor Hidayah; Saad, Shahbudin; Khodzori, Mohd Fikri Akmal; Yusof, Muhammad Hamizan; Hanapiah, Muhammad Faiz (University Malaysia Sabah, 2016)
Assessing coral morphology is to predict coral reefs conservation value. Coral lifeforms at four stations in Tioman Island were observed and recorded by using Coral Video Transect (CVT) method. The stations were Renggis and Terdau in the west coast and Benuang and Teluk Dalam in the east coast of Tioman Island. The captured images were analyzed using Coral Point Count with Excel extension (CPCe) software to find out the diversity and distribution of coral lifeforms in each study area. Three stations obtained “good” condition of reef with more than 60% of live coral coverage and one station obtained “fair” reef condition. Generally, the most dominant coral lifeform in Tioman Island is Acropora branching followed by massive. Acropora branching was the most abundance lifeform in Renggis. Terdau was dominated by massive lifeform and in the East coast, Benuang plate was the most abundant lifeform. By using the coral morphology triangle, conservation value of reefs in all four stations was predicted using the percentage of coral lifeforms. Renggis and Teluk Dalam need to be conserved the most since the reefs are classified as ruderals (fast growing but very fragile). Reef in Benuang are classified as competitor. It grows slower than ruderal but has higher tolerance. Terdau’s reef is mix of all categories.